Design and Implementation of Smart Shopping Cart Based On Web Application Technology - Jonathan Vito Setiawan; Muhammad Dawwam; Aldira Fadillah Lazuardi; Suryo Adhi Wibowo; Rissa Rahmania; Siddiq Wahyu Hidayat (School of Applied Science, Telkom University, 2024)
Due to waiting time in cashier queues, resulting in a decline in consumer satisfaction and loss of precious time. Because of this problem, we proposed the solution for reducing waiting time in the cashier queue is a tool that can identify the type of retail product and the quantity that customers will be purchasing. In creating the design, Blender is used for the 3D, and Figma is used for creating User Inteface (UI). Hardware implementation using Jetson NANO microcomputer with camera modules to capture products and Wi-Fi capabilities to enable seamless cloud integration with its web application. Implemented in parallel with hardware implementation, the software implementation focused on creating a web application that displays every product that enters the Smart Cart. A combination of sensors, wifi modules, and a microcomputer ensures optimal performance for data handling with the database. The approximate round trip connection to the database has a minimum time as small as 17ms while the maximum is 57ms and the average is 23ms.